'This place is a bus stop': Temporalities of Zimbabwean migrant men waiting at a Zimbabwe-South Africa border transit shelter. Issue 1 (March 2022) - Vanyoro, Kudakwashe
This article explores how temporal disruptions at international borders shape immobile bodies' experiences and modes of waiting by focusing on irregular Zimbabwean migrant men at the Zimbabwe-South Africa border who have arrived in South Africa but are restricted in moving further into the interior. It argues that waiting is a component of both governing these migrants as well as them seeking agency through the relationship between time, space and humanitarianism in this border regime. This shows how immobilities at 'carceral junctions' can be conceptualised as in time as much as in space. The article is based upon four months of ethnographic field research at the 'I Believe in Jesus Church' men's shelter in the border town of Musina. The intersections of immobility and temporal agency in this article contribute to a growing body of work that shows that the relationship between resistance and domination in waiting is ambivalent. This article also troubles assumptions about immobility as an experience that leads the inhabitants of humanitarian camps as well as carceral time-spaces to realise the status of 'bare life'. While imposed forces make assumptions about the future precarious, the precariousness of the future also creates multiple and new possibilities.